2023
DOI: 10.1177/11779322231154966
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS Analysis, Computational Investigation, and Antimalarial Studies ofAzadirachta indicaFruit

Abstract: Malaria is a deadly disease that continues to pose a threat to children and maternal well-being. This study was designed to identify the chemical constituents in the ethanolic fruit extract of Azadirachta indica, elucidate the pharmacological potentials of identified phytochemicals through the density functional theory method and carry out the antimalarial activity of extract using chemosuppression and curative models. The liquid chromatography-mass spectrometry (LC-MS) analysis of the ethanolic extract was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Extracts are considered active if they can extend the survival of the animal beyond 12 days. 40 Also, Faloye et al 41 reported that the survival time for treated mice in antiplasmodial studies which doubled that of the negative control, was evidence of good antiplasmodial activities of the extract. Even at the lowest dose of 100 mg/kg, the LA extract was able to triple the survival time of the animals relative to negative control and therefore could be considered as an indication of good antiplasmodial activity.…”
Section: Discussionmentioning
confidence: 98%
“…Extracts are considered active if they can extend the survival of the animal beyond 12 days. 40 Also, Faloye et al 41 reported that the survival time for treated mice in antiplasmodial studies which doubled that of the negative control, was evidence of good antiplasmodial activities of the extract. Even at the lowest dose of 100 mg/kg, the LA extract was able to triple the survival time of the animals relative to negative control and therefore could be considered as an indication of good antiplasmodial activity.…”
Section: Discussionmentioning
confidence: 98%